Learning Evaluation in Early Childhood Education During the Covid-19 Pandemic at Aisyiyah Kindergarten Babadan Sambi Boyolali in the Academic Year of 2020/2021 - Ariqoh Rizqi; Darsinah Darsinah (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
This research aims to describe 1) aspects of learning evaluation, 2) procedures of learning evaluation used, and 3) reports of learning evaluations to student parents. It is a qualitative descriptive research. The data collected are aspects, procedures, and reports of learning evaluation. Data collection uses interview and documentation techniques. Data sources are class teachers and student parents. Validity of data uses triangulation of sources and techniques. The technique of data analysis uses the interactive analysis model of Milles and Huberman. The research results show: 1) the aspects evaluated in learning consist of six development aspects and Kemuhammadiyahan, 2) the procedures of learning evaluation involve assessing children’s work sent by parents via the WhatsApp application. The only assessments carried out are daily assessments using checklist techniques, 3) and the reports of learning evaluations from the results of daily assessment recaps carried out once every six months at the end of the semester in the form of a Child Development Report Book containing descriptive reports and checklists.